Pengaruh Work Life Balance Dan Lingkungan Kerja Terhadap Semangat Kerja Pegawai Dinas Koperasi, Perindustrian dan Perdagangan (Diskoperindag) Kota Bima - Nurhasanah Nurhasanah; Firmansyah Kusumayadi; Rahmatia Rahmatia (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine whether work life balance and work environment have a positive and significant influence on employee morale at the Bima City Cooperatives, Industry and Trade Department. The research instrument used a questionnaire with a Likert scale. The population in this study was 64 employees consisting of 34 civil servants, 7 honorary employees and 23 contract employees. The sample in this research was 34 Civil Servants with the sampling technique used, namely purposive sampling technique. Data collection techniques use observation, questionnaires, documentation. Data analysis techniques use validity tests, reliability tests, multiple linear regression tests, classical assumption tests, correlation coefficient tests, coefficient of determination, t tests and f tests with the help of SPSS version 23 for Windows. The results of the research show that there is a partially significant positive influence of Work Life Balance on employee morale, there is a partial positive and significant influence of the work environment on employee morale, there is a simultaneous positive and significant influence of Work Life Balance and the work environment on employee morale in Bima City Department of Cooperatives, Industry and Trade.